Marker Assisted Selection for Bacterial Leaf Blight Resistance in Segregating Populations of Cottondora Sannalu - Magar, Manu Maya; Rani, Ch.V. Durga; Auradha, G (International Journal of Applied Sciences and Biotechnology, 2014)
The present investigation was undertaken with the objective to develop high yielding, fine grain rice varieties possessing broad spectrum durable resistance by transferring bacterial leaf blight (BLB) resistant genes viz., xa13 and Xa21 from B95-1. A popular high yielding and fine grain rice variety, MTU1010 (Cottondora Sannalu), susceptible to BLB and B95-1 carrying resistant genes for BLB (xa13 & Xa21 genes) was selected as the parent for crossing. B95-1 was verified for the presence of target genes by using gene linked primers viz., xa13 promotor and pTA 248. These primers were also used to study polymorphism between resistant (B95-1) and susceptible (MTU1010) parents. The cross viz., MTU1010 x B95-1 was affected during Rabi, 2010 and F1 progenies were confirmed during Kharif, 2011. The F1 plants confirmed as true hybrids for both the genes were advanced to F2 generation and foreground selection was done using gene linked markers. Genetic analysis in F2 populations confirmed that the genes (xa13 & Xa21) governing BLB resistance followed Mendelian inheritance. The phenotypic data analysis revealed that the plants carrying two resistance gene combinations (xa13xa13 Xa21Xa21, xa13xa13Xa21xa21) showed BLB resistance (0-2 scale), while the gene combinations viz., Xa13Xa13Xa21Xa21, Xa13Xa13Xa21xa21, and Xa13xa13Xa21Xa21, Xa13xa13Xa21xa21 showed BLB resistance (0.5-3.0). DOI: http://dx.doi.org/10.3126/ijasbt.v2i3.10570 Int J Appl Sci Biotechnol, Vol. 2(3): 229-237